القيمة التنبؤيّة للبيليروبين في الكشف عن عوز خميرة نازعة هيدروجين الغلوكوز-6-فوسفات G6PD عند حديثي الولادة - أسعد, رمال; حسين, فراس; أحمد, خزامى (Latakia University Journal -Medical Sciences Series, 2018)
We studied the correlation between neonatal jaundice and glucose-6-phosphate dehydrogenase (G6PD) deficiency in healthy full-term newborn babies in the National Obstetrics Hospital in Tartus between 2014 and 2015. The newborns were screened soon after delivery for the quantitative measurement of G6PD activity and total/indirect plasma bilirubin levels in cord blood. Only 36 babies were brought on the fifth day for follow-up and measurement of total/indirect plasma bilirubin. The overall incidence of G6PD deficiency was 5%. The mean enzyme activity in deficient infants was 9.421±0.987 U/g Hb. Our results showed a statistically significant correlation between bilirubin levels (total and indirect) on the first day of life and G6PD activity. The G6PD deficient infants had significantly higher mean TB values than G6PD normal ones (4.75±0.353 mg/dl vs. 1.714±1.179 mg/dl). The predictive values of total and indirect plasma bilirubin in detection of G6PD deficiency were 3.65 mg/dl and 2.95 mg/dl respectively. تمت دراسة العلاقة بين اليرقان الولادي وعوز خميرة نازعة هيدروجين الغلوكوز-6-فوسفات G6PD (Glucose-6-phosphate dehydrogenase) عند 45 طفلاً حديث الولادة بتمام الحمل في مشفى التوليد الوطني في طرطوس بين عامي 2014 و 2015. تم في اليوم الأول للولادة إجراء معايرة كمية لفعالية خميرة G6PD وبيليروبين البلازما الكلي وغير المباشر في دم الحبل السري. تمت إعادة 36 طفلاً فقط إلى المستشفى في اليوم الخامس من أجل إعادة معايرة لبيليروبين البلازما الكلي وغير المباشر. أظهرت النتائج أن نسبة عوز خميرة G6PD بين حديثي الولادة 5%. كما أظهرت النتائج أيضاً وجود علاقة هامة إحصائياً بين قيم البيليروبين الكلي وغير المباشر في اليوم الأول من العمر وبين مستوى فعالية G6PD، حيث كان متوسط تركيز البيليروبين الكلي أعلى بدرجة هامة إحصائياً عند الولدان معوزي G6PD منه عند الولدان الطبيعيين (4.75±0.353 ملغ/دل مقابل1.714±1.179 ملغ/دل)، وكانت القيم التنبؤية للبيلروبين الكلي وغير المباشر في الكشف عن عوز G6PD هي 3.65 ملغ/دل، و 2.95 ملغ/دل، على التوالي.